2022
DOI: 10.1155/2022/9406497
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of the Efficacy and Safety of Tranexamic Acid in Spinal Surgery

Abstract: Objective. The safety and effectiveness of topical tranexamic acid in spinal surgery has not yet been reached, and further research is needed to confirm it. This study is aimed at detecting the effectiveness and safety on the tranexamic acid in spinal surgery. Methods. The Cochrane Library, PubMed, Embase, CNKI, and other databases were searched. The search time was from 2016 to 2019. All randomized controlled trials comparing the topical tranexamic acid group and the control group were collected. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, there is still a concern about the safety of high dose of TXA in surgery patients. [67] Bao et al [68] compared the efficacy and safety of TXA in spinal surgery and results found that TXA significantly reduce perioperative blood loss without increasing the thrombosis events. Thus, TXA can be applied for reducing blood loss in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a concern about the safety of high dose of TXA in surgery patients. [67] Bao et al [68] compared the efficacy and safety of TXA in spinal surgery and results found that TXA significantly reduce perioperative blood loss without increasing the thrombosis events. Thus, TXA can be applied for reducing blood loss in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…V posledním desetiletí strmě narůstá počet studií, které hodnotí efekt tranexamové kyseliny na redukci perioperačního krvácení u konkrétních chirurgických výkonů různých oborů, jakožto i u spinálních operací. I přes to že již řada metaanalýz potvrzuje příznivý vliv tranexamové kyseliny na redukci krevní ztráty u spinálních operací (2,6,12,17,18), několik málo studií ale takto jednoznačný příznivý vliv nepotvrdilo (3,10). Otázkou stále zůstává dávka, způsob podání a typ výkonu, kdy je podání tranexamové kyseliny přínosné.…”
unclassified